Forensic Determination Of Ethanol In Import And Local Prepared Vinegar For Halal In Accordance With Shafi’i School Of Jurisprudence - Baharuddin A.S.; Amin, N.S.M.; Ruskam, A.; Yacob, A.R. (RYNNYE LYAN RESOURCES, 2024)
Indexed by Scopus/MyCite